2018
DOI: 10.1021/acsomega.8b01513
|View full text |Cite
|
Sign up to set email alerts
|

1H-1,2,3-Triazole Tethered Nitroimidazole–Isatin Conjugates: Synthesis, Docking, and Anti-Proliferative Evaluation against Breast Cancer

Abstract: 1H-1,2,3-Triazole tethered imidazole–isatin and imidazole–isatin–thiosemicarbazone conjugates were synthesized and evaluated against MCF-7 and MDA-MB-231 cell lines. Antiproliferative activities of the synthesized conjugates revealed an optimum combination of longer alkyl chain length as spacer and a halogen-substituent on the isatin ring as a pre-requisite for good activity. The compound 6g with an optimum combination of chloro-substituent at C-5 position of isatin ring and a butyl chain length proved to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…In a previous study, nitroimidazole derivative of polypyridyl ruthenium complex was employed in order to evaluate the anticancer activity against breast cancer (4T1) and A549 cell lines and they reported that the tested cell lines were strongly inhibited with IC50 ranging from 1.5 to 18.8 µM [20], a range covering the LC 50 values exhibited by N-methyl and N-ethylnitroimidazoles. In a study conducted by Kumar et al,2, Tethered Nitroimidazole−Isatin Conjugates showed IC50s of 54.25 and 26.12 μM against MCF-7 and MDA-MB-231 cell lines, respectively, when a butyl alkyl chain length as a spacer and a halogen-substituent on the isatin ring was placed [6]. LC50 values reported in our study are below those reported by Kumar et al, reported that the activity tends to increase with the increase in chain length in contrast with our results where activity decreased and was maintained with increasing chain length, against A549 and MDA-MB-231 cell lines, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, nitroimidazole derivative of polypyridyl ruthenium complex was employed in order to evaluate the anticancer activity against breast cancer (4T1) and A549 cell lines and they reported that the tested cell lines were strongly inhibited with IC50 ranging from 1.5 to 18.8 µM [20], a range covering the LC 50 values exhibited by N-methyl and N-ethylnitroimidazoles. In a study conducted by Kumar et al,2, Tethered Nitroimidazole−Isatin Conjugates showed IC50s of 54.25 and 26.12 μM against MCF-7 and MDA-MB-231 cell lines, respectively, when a butyl alkyl chain length as a spacer and a halogen-substituent on the isatin ring was placed [6]. LC50 values reported in our study are below those reported by Kumar et al, reported that the activity tends to increase with the increase in chain length in contrast with our results where activity decreased and was maintained with increasing chain length, against A549 and MDA-MB-231 cell lines, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment modalities are surgical resection, radiation therapy, hormone therapy, anti-hormone therapy, combined therapy as chemotherapy and radiation therapy, where the most commonly used chemotherapeutic agents are cytotoxic agents for cancer cells [4]. Some of these agents correspond to the imidazole compounds, which are developed towards their application in medicinal chemistry due to their pharmacological properties, such as anticancer activity with high efficacy and low toxicity [5,6]. In this context, the imidazole ring containing two nitrogen atoms and desirable πconjugated backbone can interfere with DNA synthesis, altering enzymes involved in DNA replication and the expression of genes associated with cancer cell growth such as tumor suppressor and cell cycle genes [7].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer activity of 1,2,3‐triazole linked isatin–imidazole hybrids 18 (IC 50 : 70.71 and 70.40 μM, MTT assay) and 19a–c (IC 50 : 16.06–70.71 μM) against MCF‐7 and MDA‐MB‐231 cancer cell lines was comparable to that of the reference tamoxifen (IC 50 : 50 and 75 μM). [ 76 ] Hybrid 18 was less active than the corresponding carbonyl analog 19b (IC 50 : 20.76 and 16.06 μM), implying thiosemicarbazone at the C‐3 position of isatin moiety was detrimental to the activity. The length of the alkyl linker between the isatin and 1,2,3‐triazole motifs influenced the activity greatly and the longer linker was preferred.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“…13 The methodology was further extended towards evaluating the anti-proliferative efficacy of 1H-1,2,3-triazole linked nitro-imidazole-isatin and isatin-ferrocenyl chalcone conjugates. 14,15 In continuation to our recent reports on the synthesis of molecular conjugates with biological relevance and their evaluation, [16][17][18] the present manuscript encompasses the design, synthesis and anti-proliferative evaluation of 1H-1,2,3-triazole linked THbC-isatin conjugates, as depicted in Fig. 2, against MCF-7 and MDA-MB-231 cell-lines using MTT assay.…”
Section: Introductionmentioning
confidence: 96%